Hubungan Kepuasan Kerja Dengan Produktivitas Pada UMKM Tahu Sumedang Uuh - Sri Devi Sigiro; Vicka Arvianti; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this observation visit is to increase students' knowledge of real conditions in the industrial world. Productivity is the sum of the final results or also known as output. The purpose of this productivity is to find out and measure whether the productivity has increased or not. Job satisfaction is an employee attitude that is shown to express satisfaction at work, so why job satisfaction has a lot to do with productivity. The goals of job satisfaction include getting an appropriate salary, career advancement, getting appreciation from the work boss, and so on. The success of a company is largely determined by the work productivity produced by each individual employee, job satisfaction is very closely related to work productivity, because maximum job satisfaction will create individual comfort at work. The results of industrial visits to UMKM Tahu Sumedang Pak Uuh where employees will experience a decrease in productivity if job satisfaction is not maximal. The method used by the author is using the field research method, where industrial visits go directly to the field, namely in Sumedang Pak Uuh Tofu to obtain relevant data, by collecting data by meeting directly with the owner of Sumedang Pak Uuh Tofu.Â